INTEGRASI AGAMA DAN SAINS: Tela’ah Pemikiran Konsep Pendidikan Islam Imam Jalaluddin As-Suyuti dan Implementasinya di Pondok Pesantren Annuqayah Sumenep Madura - Ahmad Shiddiq (Institut Kariman Wirayudha Sumenep, 2016)
The dichotomy of education in Indonesia is a problem in constructing a paradigm of integrative education. Pesantren which has been symbolized as an Religion of educational institution, actually is not just a religious education. Pesantren is a place of learning knowledge of the world and the hereafter. Integration of Religion and Science in education Pesantren (Implementation Book Itman dirayah ad-li al-Qurra 'Annuqayah by Imam Jalaluddin As-Suyuti in pesantren Annuqayah).This article uses two approaches methodology: First, the library reseach (library research), is used to facilitate the course of research-based literature, especially the book of Itman ad-dirayah li al-Qurra 'Annuqayah by Imam Jalaluddin As-Suyuti as the cornerstone of the conception of knowledge boarding while the second, field research (fieldwork) as a way to obtain data on the implementation of the conception of the book of knowledge boarding Itman dirayah ad-li al-qurra 'Annuqayah by Imam Jalaluddin as-Suyuti in pesantren Annuqayah Guluk-guluk Sumenep. These two approaches are done for research to be carried out, are Conceptual and Applied. So this research was more holistic and integrative. Imam Jalaluddin Assuyuti view that there are fourteen (14) disciplines / knowledge which includes religious sciences, sciences Arabiyah and general sciences, namely Humanities, Medicine and Anatomy. Pondok Pesantren Annuqayah Sumenep is an institution of Islamic education has the vision and mission and the foundation of integrative education between science and religion with the 14 knowledge contained in the book Itman ad-dirayah li al-Qurra 'Annuqayah are then summarized in kitam mandhumatun Annuqayah work Kiai Mahfudh Husaini.